Pentingnya Manajemen Waktu Bagi Siswa Siswi Di SMK PGRI 31 Legok Kabupaten Tangerang - Diana Silaswara; Agus Kusnawan; Metta Susanti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Nowadays, many people, both young and old, claim to have mental health problems due to stress. That is one of the reasons why we must have and manage time management well. We hope that by learning and getting used to time management in everyday life, we can be more organized and discipline in carrying out the work assigned to us and do everything without feeling forced or burdened.